2018
DOI: 10.1016/j.jbiotec.2018.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of centrate for the outdoor production of marine microalgae at pilot-scale in flat-panel photobioreactors

Abstract: The outdoor production of marine microalgae biomass in pilot scale flat panels photobioreactors, under not sterile conditions and using centrate as nutrients source, was studied. Experiments were performed modifying the centrate percentage, dilution rate and orientation of the photobioreactors. The strain Geitlerinema sp. was that one prevailing independently of the culture conditions. The higher productivity of 47.7 g m·day dry weight and photosynthetic efficiency of 2.8%, was achieved when using 20% centrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 49 publications
1
9
0
1
Order By: Relevance
“…While tubular PBRs showed 5 different species (Romero Villegas et al, 2017), flat-panels PBRs exhibited only two strains (Nannochloropsis g. and Geitlerinema sp.) (Romero- Villegas et al, 2018), whereas previous studies showed that monocultures of Nannochloropsis g. (Ledda et al, 2015) and Scenedesmus sp. (Morales-Amaral et al, 2015) could be obtained using wastewater in raceway PBRs.…”
Section: Microalgae Population Strainsmentioning
confidence: 84%
“…While tubular PBRs showed 5 different species (Romero Villegas et al, 2017), flat-panels PBRs exhibited only two strains (Nannochloropsis g. and Geitlerinema sp.) (Romero- Villegas et al, 2018), whereas previous studies showed that monocultures of Nannochloropsis g. (Ledda et al, 2015) and Scenedesmus sp. (Morales-Amaral et al, 2015) could be obtained using wastewater in raceway PBRs.…”
Section: Microalgae Population Strainsmentioning
confidence: 84%
“…In another study, microalgae were cultivated in controlled media to simulate the synthetic wastewater and the single-stage culture systems. The study showed a production rate of 132.8 mg/day for biomass (15).…”
Section: Introductionmentioning
confidence: 90%
“…Regarding PBRs, north–south orientation has been reported to be more favorable for latitudes over 35°N, while closer to the equator, the east–west orientation contributes to increasing the photosynthetic rate due to higher solar radiation (Romero‐Villegas, Fiamengo, Acién Fernández, & Molina Grima, 2018).…”
Section: Microalgae Cultivationmentioning
confidence: 99%
“…There are two main ways to operate microalgae‐based wastewater treatment systems: without biomass retention. In this case, HRT is equal to SRT (Galès et al, 2019; Romero‐Villegas, Fiamengo, Acién Fernández, & Molina Grima, 2018). Since microalgae usually present lower growth rates than bacteria, that is, in the range of 0.4–0.9 days −1 (Pachés et al, 2020; Ruiz et al, 2013), relatively long HRTs are needed to avoid microalgae washout: 3.3–10 days (Arbib et al, 2017; González‐Camejo, Jiménez‐Benítez, et al, 2019a).…”
Section: Microalgae Cultivationmentioning
confidence: 99%